2018
DOI: 10.1080/19336918.2018.1494997
|View full text |Cite
|
Sign up to set email alerts
|

A biophysically-defined hyaluronic acid-based compound accelerates migration and stimulates the production of keratinocyte-derived neuromodulators

Abstract: Hyaluronic acid (HA) preparations are widely used in clinical practice and recent data suggest that commercially available HA-based compounds promote ulcer re-epithelialization and induce pain relief. However, the pathophysiological basis of these effects remains poorly understood. In the present study, we investigated the biophysical, biomolecular and functional properties of a HA preparation combined with a pool of collagen precursor synthetic aminoacids, namely l-proline, l-leucine, l-lysine and glycine (Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…This gel, thanks to its local administration and substantivity, promotes the deposition of components of the extracellular matrix and the production of cytokines, thus accelerating the wound healing process. Moreover, hyaluronic acid binds many water molecules, and so also improves tissue hydration and cellular resistance to mechanical damage [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This gel, thanks to its local administration and substantivity, promotes the deposition of components of the extracellular matrix and the production of cytokines, thus accelerating the wound healing process. Moreover, hyaluronic acid binds many water molecules, and so also improves tissue hydration and cellular resistance to mechanical damage [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of HA constituents used; Mucosamin ® , H-MW-HA (1% and 5%, v/v), xl-HA 5/5, xl-HA 30/30, and xl-HA 100/100 (0.01% v/v) and xl-HA (100/100). Concentrations of all HA constituents were chosen for potential safe efficacy, as determined by preliminary experiments (data not shown) and potential therapeutic efficacy of HA-based compound (Mucosamin ® ) [ 28 , 76 ]. To determine the potential protective effect of HA constituents on H 2 O 2 -induced damage in oral keratinocyte cells, cell viability was assessed using fluorescein diacetate (FDA) fluorescent assay [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…In one study, analysis of microarray data demonstrated that cultured keratinocytes had a functional neuroendocrine machinery, and this was confirmed by testing the secretion of six neuroactive molecules by ELISA, namely α-MSH, β-endorphins, melatonin, substance P, cortisol, and neurotensin. Interestingly, hyaluronic acid regulated the production of several neuropeptides, including β-endorphins, in vitro [ 57 ]. Pro-enkephalins and met-enkephalin are also expressed in skin keratinocytes in vivo [ 58 ].…”
Section: Opiate Peptidesmentioning
confidence: 99%